P150 Partnerships between services can support survivors of sexual abuse, violence and exploitation. (8th June 2017) - Harding, Rebecca; Phattey, Jara; Thompson, Lisa; Langham, Yvonne; Caswell, Rachel
Abstract : Introduction: The ASC Clinic (Abuse Survivors Clinic) offers specialised services to patients who have been affected by sexual violence. It is provided by Umbrella NHS Sexual Health Service and third sector partner RSVP (the Rape and Sexual Violence Project). The ASC offers emotional and medical support to survivors of sexual exploitation, coercion, abuse and violence. This is a review of the experience gained in the first year. Methods: A retrospective review of the electronic case notes for all patients who attended the ASC, November 2015-2106. Results: 46 female, 8 male, 1 transgender attended with 6 <18years. The majority of patients (41) were referred by Sexual Health staff, and others were from SARC (9), RSVP (1), another hospital (1), and 1 patient self-referred. One of the patients was experiencing on-going sexual violence at the time of attendance, 18 had experienced it within the past month, 14 between 1 month and 1 year before being seen, and 22 more than 1 year previously. Nearly all (5) of the under 18-year olds were referred to Safeguarding teams, and 9 of the adults. The majority accepted services from both partner agencies. 128 appointments were made with 63 attendances (DNA rate 49%). Discussion: We are increasingly aware of the numbers of people who have experienced sexual violence. The ASC provides a dedicated service for this vulnerable group. The innovative approach of working with the third sector helps combine experience and expertise enabling more holistic care. Further work is needed to improve clinic accessibility and to evaluate patient experience.